Effects of the COVID-19 pandemic on timely care for extrauterine pregnancies: A retrospective analysis - Matan Anteby; Liel Van Mil; Nadav Michaan; Ido Laskov; Dan Grisaru (Elsevier, 2021)
Background: The COVID-19 pandemic may have taken a toll upon the rate of extrauterine pregnancy (EUP)-related admissions and emergent surgeries. Methods: This retrospective study compared current and past visits to the emergency services of a large metropolitan university-affiliated medical center in Tel-Aviv, Israel. Data on EUP-related and regular early pregnancy care-related presentations to the emergency department (ED) during the COVID-19 pandemic were collected and compared to a historical control group admitted during 2018-2019. The primary outcome was the rate of ruptured EUP. Secondary outcomes included the rate of EUPs requiring surgery, symptoms, blood products, blood loss, embryonic heart rate, β-HCG levels, and intensive care unit transfer. Findings: During the COVID-19 pandemic there was a 28.3% reduction in women seeking early pregnancy and emergent gynecological medical care. ED visits due to suspected EUP were similar: After exclusion, the study group comprised of 100 women and the combined control group from previous years included 208 women with confirmed EUP. Baseline maternal characteristics were similar between the groups. The rate of ruptured EUP's was significantly more common during the COVID-19 pandemic than in previous years [odds ratio (OR) 2•403 (1•272-4•539), p = 0•006]. Moreover, during the pandemic patients admitted due to EUP were significantly more symptomatic [OR 1•815 (1•072-3•074), p = 0•017] and had more blood loss demonstrated as substantial hemoglobin decline [OR 2•441 (1•07-5•565), p = 0•028] as well as hemoperitoneum during surgery [OR 2•672 (1•095-6•52), p = 0•035] The number of women receiving blood products was higher in the study group yet not reaching statistical significance [7% vs 3•4%, OR 2•161 (0•737-6•339) p = 0•128]. The overall rate of surgically treated EUP was similar between the groups [OR 1•070 (0•660-1•734), p = 0•439] and there was no significant difference in non-surgical management. Interpretation: The COVID-19 pandemic has a toll on early pregnancy emergent care due to EUP with a significantly higher risk of tubal rupture and morbidity. Physicians should expect delayed presentation of symptomatic EUP and act accordingly. Funding: This research received no funding.